PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE SAMSUNG PADA MAHASISWA FAKULTAS EKONOMI SEMESTER V DAN SEMESTER VII UNIVERSITAS ABDURACHMAN SALEH - Karnadi Karnadi; Miswati Miswati (Growth, 2018)
This study aims to (1) to determine the effect of product quality variables, prices and brand image partially to the purchase decision (2) to determine the effect of product quality variables, price and brand image simultaneously to purchase decision (3) to know the dominant variable against the purchase decision. This research consist of 3 independent variable (X) that is product quality (X1), price (X2), and brand image (X3) and 1 dependent variable (Y) that is purchasing decision. Methods of data collection was done by observation method, and the distribution of questionnaires to students of semester V and VII of Abdurahman Saleh Situbondo University. The result of research is multiple linear regression equation Y = 1,435E-16 + 0,359X1 + 0,269X2 - 0,198 X3 + e. Test t obtained positive significant effect of product quality equal to 3,287 and equal to 1,994, equal to 2,454 and equal to 1,994, and significant negative effect of brand image equal to equal to -2,067 equal to 1,994 to purchase decision. Test simultaneously obtained by equal to 14,125 equal to 2,74. The dominant test found that product quality variables have the most dominant influence to the purchase decision of 3.287. Coefficient of Determination of 37.7%.